The effects of yoga on functionality appreciation and additional facets of positive body image. (September 2020) - Alleva, Jessica M.; Tylka, Tracy L.; van Oorsouw, Kim; Montanaro, Erika; Perey, Iris; Bolle, Cheyenne; Boselie, Jantine; Peters, Madelon; Webb, Jennifer B.
Highlights: Young women were randomized to a Hatha yoga programme or waitlist control group. Yoga practice did not lead to improvements in functionality appreciation. Functionality appreciation did not mediate yoga's effects on positive body image. Instead, yoga's effects on positive body image were mediated by positive embodiment. Yoga's effects on positive body image were also mediated by self-objectification. Abstract: This study investigated the effects of yoga on functionality appreciation, and the potential mechanisms that could explain the impact of yoga on additional facets of positive body image. Young adult women ( N  = 114; M age  = 22.19) were randomised to a 10-week Hatha yoga programme or waitlist control group. Participants completed measures of functionality appreciation, body appreciation, body compassion, appearance evaluation, self-objectification, and embodiment at Pretest, Midtest, Posttest, and 1-month Follow-Up. Follow-up data could not be analysed due to high levels of attrition. The remaining data showed that, compared to the control group, women in the yoga programme experienced lower self-objectification at Midtest and greater embodiment over time. Further, all participants experienced improvements in body appreciation, body compassion, and appearance evaluation over time, regardless of their assigned group. Lower self-objectification contributed to improvements in body appreciation and body compassion. In addition, greater embodiment contributed to improvements in body appreciation, body compassion, and appearance evaluation. Contrary to our expectations, yoga did not lead to increased functionality appreciation, nor was functionality appreciation a mediator of the impact of yoga on positive body image. Instead, lower self-objectification, and greater embodiment, drove improvements in positive body image.